The influence of some clinical and morphological prognosis factors on the 5-year survival of patients with stage I cervical cancer - E. V. Makarova; M. A. Senchukova (Исследования и практика в медицине, 2019)
Purpose of the study. To analyze the treatment long-term results of patients with cervical cancer (CC) depending on the clinical and morphological characteristics of the disease.Patients and methods. 75 patients with stage I cervical cancer at the age of 21 to 76 years, were included in this retrospective study. All patients have been operated at the first stage of treatment in the Orenburg Regional Clinical Oncology Center from 2008 to 2013. Patient data was obtained from patient card and the "cancer-register". The statistical analis of the results was performed using the Statistica 6 software.Results. Recurrence of disease was detected in 7 patients and 7 patients died after treatment. 5-year relapse-free survival (RFS) and overall survival (OS) were 90,3%. 5-year RFS was: 95.2% and 66.0% — in depth of invasion of 10 mm or less and more than 10 mm (p=0.0004); 94.4% and 89.5% — in stages IA and IB (p>0.4) and 80.6% and 97.6% — in the presence and absence of adjuvant radiation therapy (p=0.002), respectively. 5-year OS was: 96.7% and 47.0% — in depth of invasion of 10 mm or less and more than 10 mm (p=0.00001); 97.0% and 84.2% — in stages IA and IB (p=0.07); 80.6% and 97.6% — in the presence and absence of adjuvant radiation therapy (p=0.02), respectively. There were no recurrence in 11 patients with IB stage, who did not receive adjuvant RT and, but ones were observed in 6 patients with stage IA — IB, who received the adjuvant RT.Conclusion. These results indicate that the use of only clinical and morphological factors is not sufficient to accurately assess of the CC prognosis and the search for new markers of the CC recurrence risk has not lost its relevance.